ProMMP-9 (92 kDa gelatinase) in vitreous fluid of patients with proliferative diabetic retinopathy - Kosano, Hiroshi; Okano, Tadashi; Katsura, Yoshiya; Noritake, Masayuki; Kado, Seijiro; Matsuoka, Takeshi; Nishigori, Hideo (Life sciences (1973), 1999)
Matrix metalloproteinases (MMPs) are implicated in tissue destruction during various pathophysiologic conditions. The vitreous body is a gel-like extracellular matrix that undergoes liquefaction during aging and pathological processes. To investigate the pathogenic role of MMPs in proliferative diabetic retinopathy (PDR), we studied 73 eyes from PDR patients and 25 eyes from patients with non-diabetic ocular diseases. Vitreous MMPs were measured by zymography. Retinopathy was assessed by ophthalmoscopy and PDR was classified into 3 stages, ‘naked’, ‘active’ and ‘quiescent’. Although proMMP-9 was expressed in only 8% (2/25) of non-diabetic patients, it was expressed in more than 80% (38/47) of ‘active’ PDR patients and still expressed in 60% (9/15) of those with ‘quiescent’ PDR. Vascular endothelial growth factor (VEGF) in vitreous fluids was undetectable (<0.16 ng/ml) in most of the non-diabetic patients, and was maximally elevated in the ‘active’ PDR patients (mean = 2.20 ng/ml, range; 0.16–7.61), declining in patients with ‘quiescent’ PDR (1.04 ng/ml, 0.16–3.77). These results suggest that MMP-9 is one of the noteworthy factors in relation to the progress of PDR, as well as angiogenic cytokines such as VEGF.